A temática da nanociência e nanotecnologia na formação inicial de professores de física abordada nas Instituições de Ensino Superior UFSC e UFMA - COSTA, Erika Santos da (2020)
The presence of terms nanoscience and nanotechnology has appeared more frequently in everyday life and countless debates are held focusing on this knowledge, which has been transforming the scientific and technological reality today. In this perspective, this research aims to analyze the teachers' conceptions about nanoscience and nanotechnology and investigate the teaching practices developed in the approach of these themes in the Physics Degree courses offered by the Federal University of Maranhão (UFMA) and Federal University of Santa Catarina (UFSC). This research is divided into two moments: the first is for documentary research in the curricular matrix and in the Pedagogical Political Project of the Physics Degree Course of the aforementioned universities. The second moment was reserved for the analysis of the conceptions of professors in practice on nanoscience and nanotechnology. The methodological approach was centered on the qualitative approach, based on two instruments for data collection, the questionnaire and the semi-structured interview, which were treated from the perspective of Content Analysis by Bardin (2011). The results revealed that the participating teachers have coherent theoretical conceptions about science at the nanoscale, are able to identify the technological applications originating from nanoscience and understand the specifications that the terms nanoscience and nanotechnology present. Teachers list, as main difficulties in approaching nanoscience in the classroom, the absence of didactic material with easy to understand language, outdated curricula and exemption from the theme in initial training. Through the analyzed data, it can be seen that the teaching of this theme has been developed essentially in a theoretical way and that the main methodological resource used in the teaching of this science are books in the field of Physics. The emergence of the nanoscience and nanotechnology approach in the classroom has become relevant and necessary. This is justified by the impacts of science on the nanoscale and its applications on society, the environment, the economy and, consequently, on human life.